Practical lessons in emergency and emergency in the training of nursing academic – esperience report (Research, Society and Development, 2020)
Introduction: The practical classes in urgency and emergency reports the importance in the formation of the academic within the university environment. Objective: to report experiences lived by students, including maneuvers in urgency and emergencies. Methods: This is a descriptive, exploratory study of the experience report type. Study was developed by academics, aiming at practical and scientific contents, approaching Paulo Freire's theory of autonomy of pedagogy, where he emphasizes ethics and teaching-learning in the application of elaborated and theoretical practices. Result and discussion: The report of experience in urgency and emergency aims at the importance of training future nursing professionals, showing teaching-learning strategies, seeking skills in activities, carrying out interventions and contributions for students and their self-confidence in simulators, showing great emphasis in the protocols taught and understood as an example ACLS and Manchester protocol that are used. Conclusion: Urgency and emergency is the gateway to large hospitals and emergency rooms, soon it becomes what most calls the attention of most students, with this we tried to focus on urgent and emergency practices in which students university students participated. Emphasizing Paulo Freire's theory of autonomy pedagogy, where both parties learn and teach.